Edukasi Keamanan Siber: Melindungi Data Diri Dan Mengenali Modus Penipuan Di Media Sosial Facebook Pada Ibu-Ibu Pkk Desa Bukit Subur Merangin - Ichsandi; Alhaq, Hawari; Yanto, Widja; Indria, Lily; Maria Ulfa, Adinda (PT. Meja Ilmiah Publikasi, 2025)
Cybersecurity is a crucial issue in the digital era, especially for communities actively using social media platforms such as Facebook. The PKK mothers of Bukit Subur Village, Merangin, represent a group vulnerable to fraud and misuse of personal data online. This community service activity aims to enhance the understanding and awareness of PKK mothers regarding the importance of protecting personal data and recognizing various fraud schemes prevalent on Facebook. The methods employed include interactive education through counseling, discussions, and case simulations. The results of the activity show an increase in participants' knowledge and vigilance towards cybersecurity risks, as well as their ability to identify and avoid fraud schemes on social media. This initiative is expected to foster a better digital literacy culture within the Bukit Subur Village community.